Modulation strategies for an open-end winding induction machine fed by a two-output indirect matrix converter - Riedemann, Javier; Andrade, Ivan; Pena, Ruben; Blasco Giménez, Ramón; Clare, Jon C.; Melin, Pedro; Rivera, Marco (Elsevier, 2016)
This paper presents a two-output indirect matrix converter feeding an open-ended winding induction machine. The modulation strategy for the converter input stage, which provides the DC voltage for the output stages, exploits the capability of the input rectifier to produce different DC voltage levels. Moreover, this paper includes a space vector modulation strategy for the converter output stages intended to eliminate the zero sequence load voltage. Furthermore, in order to decrease commutation losses, output stage commutation will take place at reduced voltage when load voltage requirements are low. Modulation strategies and overall system operation are verified via simulation in a PSim/Matlab platform with the machine operating under an open loop V/f control strategy. Experimental results are also presented to validate the control strategies.